Bioassay and dose measurement in UV disinfection. - Qualls, R G (1983)
A bioassay method was developed to measure the average intensity within a UV disinfection reactor. The survival of spores of Bacillus subtilis was determined as a function of UV dose to prepare a standard curve. Spores were added to unknown systems, and the survival rate was used to determine the average intensity. A modification was used for flow-through reactors by which spores were injected as a spike and collected at a known time after injection. A point source summation method for calculating intensity was verified by bioassay measurements in a simple cylinder. This calculation method was also applied to multiple-lamp reactors.